Food Order Information System at Coffee Shop by Applying the Multilever Feedback Queue Algorithm - Zen, Muhammad; Davy Anggara Saragih, Muhammad; Irwan (Cattleya Darmaya Fortuna, 2024)
The rapid development of business encourages every entrepreneur to make a different form of service to attract customers. Fast service is its own attraction for customers. The application of a queue or scheduling system in the kitchen or chef can be done to avoid the accumulation of food orders in the kitchen or chef so that the time for serving food can be done quickly. Multilevel Feedback Queue is one of the scheduling algorithms on CPU scheduling in the computer's Operating System. The Multilevel Feedback Queue algorithm allows the process to move queues. If a process takes too long to consume CPU, then it will be moved to a lower queue thus the process of CPU interaction becomes less and the time is fast. In this study, a Web-based food ordering application was developed by applying a Multilevel Feedback Queue to create a food order queue.